HAMBATAN DALAM PELAKSANAAN PEMBUATAN SERTIPIKAT ELEKTRONIK DI KANTOR BADAN PERTANAHAN NASIONAL KABUPATEN KARANGANYAR - Julia Syarafina; Susilowardani (Bajang Institute, 2025)
The transformation of land services from a manual system to a digital one is a crucial step in modernizing public bureaucracy in Indonesia. One tangible form of this transformation is the implementation of electronic land certificates based on the Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) Number 1 of 2021. This study aims to identify and analyze the obstacles in the implementation of electronic certificates at the BPN Office of Karanganyar Regency. The method used is an empirical juridical approach by collecting data through literature studies and interviews with BPN officers and service applicants. The results show that the main obstacles in implementing electronic certificates include limited technological infrastructure, low digital literacy among the public, suboptimal readiness of human resources, and the geographical conditions of Karanganyar Regency which hinder effective dissemination. Based on Soerjono Soekanto’s theory of legal effectiveness, it was found that the success of electronic certificate implementation is significantly influenced by five key factors: the legal framework, law enforcement, facilities and infrastructure, society, and culture. The conclusion of this study emphasizes the importance of strengthening infrastructure and public education as initial steps toward inclusive and effective land digitalization